Land abandonment and changes in snow cover period accelerate range expansions of sika deer. Issue 21 (5th October 2016) - Ohashi, Haruka; Kominami, Yuji; Higa, Motoki; Koide, Dai; Nakao, Katsuhiro; Tsuyama, Ikutaro; Matsui, Tetsuya; Tanaka, Nobuyuki
Abstract: Ongoing climate change and land‐use change have the potential to substantially alter the distribution of large herbivores. This may result in drastic changes in ecosystems by changing plant–herbivore interactions. Here, we developed a model explaining sika deer persistence and colonization between 25 years in terms of neighborhood occupancy and habitat suitability. We used climatic, land‐use, and topographic variables to calculate the habitat suitability and evaluated the contributions of the variables to past range changes of sika deer. We used this model to predict the changes in the range of sika deer over the next 100 years under four scenario groups with the combination of land‐use change and climate change. Our results showed that both climate change and land‐use change had affected the range of sika deer in the past 25 years. Habitat suitability increased in northern or mountainous regions, which account for 71.6% of Japan, in line with a decrease in the snow cover period. Habitat suitability decreased in suburban areas, which account for 28.4% of Japan, corresponding to land‐use changes related to urbanization. In the next 100 years, the decrease in snow cover period and the increase in land abandonment were predicted to accelerate the range expansion of sika deer. Comparison of these two driving factors revealed that climate change will contribute more to range expansion, particularly from the 2070s onward. In scenarios that assumed the influence of both climate change and land‐use change, the total sika deer range increased by between +4.6% and +11.9% from the baseline scenario. Climate change and land‐use change will require additional efforts for future management of sika deer, particularly in the long term. Abstract : The population of Japan's sika deer (Cervus nippon Temminck), a large herbivore, has increased rapidly in the last few decades, and climate change, together with abandonment of land in rural areas, will likely add to its range expansions. Our results showed that both climate change and land‐use change had affected the range of sika deer in previous decades. In the next 100 years, the decrease in snow cover period and the increase in land abandonment were predicted to accelerate the range expansion of sika deer.